Are the most influential websites peer-produced or price-incentivized? Organizing value in the digital economy. (July 2022) - Pazaitis, Alex; Kostakis, Vasilis
In 2006, Harvard Law School Professor Yochai Benkler proposed a wager to technology and society author Nicholas Carr. Benkler argued that by 2011 the most influential websites would be based on content produced by people engaged in peer production. Carr maintained that the lure of money and the corporate hierarchies will be more effective. So, after 15 years, who has really won the bet? Are the most influential websites peer-produced or price-incentivized? To address these questions, this paper discusses what peer production is in relation to price-incentivized production. The Carr-Benkler wager is used as a lens to examine the current social and political struggles in the digital economy, to unveil the adversary value systems underneath and the respective implications for organization. We conclude with some reflections on the controversies and ambiguities of peer production and a call for critical scholarship to engage in a deeper discussion on value and organization in the digital economy.